Wasiat Wajibah Bagi Suami Murtad Dalam Pendekatan Teleologik Menuju Realisme Hukum (Suatu Analisis Terhadap Putusan MA Nomor 331 K/Ag/2018) - Hazmi, Raju Mohammad; Adhha, Nurul; Kamarusdiana, - (UI Scholars Hub, 2021)
The Compulsory will (wasiyah wajibah) is one of the products of ijtihad in the field of contemporary Islamic jurisprudence. The case of compulsory wills is also included in the sub-discussion of inheritance in family or civil law in several countries with a majority Muslim community. The provision of a mandatory will appears as an alternative to several inheritance problems, such as the right to inheritance for heirs of different religions, children and adoptive parents. This condition is faced with the reality of the inheritance law of a society that cannot be separated from the structure, norms and traditions of a society that has lived (living law) for years. One of the practices of compulsory will that is in the spotlight in Indonesia is the case of compulsory will in the Supreme Court Decision Number 331 K / Ag / 2018. This decision is an elected decision of the Supreme Court (landmark decision) which changes the decision of the Banten High Religious Court No. 78 Pdt.G / 2017 PTA Btn regarding the distribution of inheritance for the husband of the heir who has apostatized.